Isolation and characterization of microorganisms from a landfarming of the province of san luis with potential capacity for use in bioaugmentation - Salinas, A. (2023)
The final disposal of industrial effluents with organic or inorganic compounds is a concern for companies and governments. Consequently, in recent decades, different methodologies have been used to reduce them, without causing damage to the environment, among which are bioremediation processes. Landfarming is an ex-situ bioremediation treatment process that is carried out in the upper zone of the soil. In San Luis Province there is a landfarming that receives effluents from chemical industry and has been used for more than 10 years. The aim of this work was to isolate microorganism from a landfarming soil with the capacity to tolerate the environmental stresses which can favor increasing and accelerating landfarming processes. The samples were collected in two stages, during the winter period of 2022: the first was taken from the supernatant of the effluent after its discharge; the second from the mud generated in the mixture of soil and effluent, after 5 days of discharge. The sampling points were 3 at different distances from the discharge of effluents. Two approaches were utilized to isolate microorganism from the landfarming soil: a direct isolation approach in EG medium following the streaked-on agar plate and enrichment approach in liquid medium incubated a 30°C, 150 rpm for 72 h. While, using a direct isolation approach only 12 morphotypes were isolated, using enrichment approach 15 morphotypes were isolated. To characterize the isolates, the characteristics of the colonies, the cells and the Gram coloration in the case of bacteria were taken into account. The isolates will be molecularly identified. It is well established that only approximately 1% of microorganisms on Earth can be readily cultivated in vitro. But this work aims to use microorganisms in bioaugmentation process, so it only focused on culturable microorganisms. These preliminary results show that landfarming has an active microbiota and it is feasible to isolate microorganisms that can be used in bioaugmentation processes with native strains